Days and Nights: Class, Gender and Society on Notre-Dame Street in Saint-Henri, 1875-1905 - Lord, Kathleen (McGill University, 2000)
The everyday life of people on the street has not received the attention it deserves in the history of late nineteenth and early twentieth-century Quebec. This dissertation joins a small number of recent studies which redress this omission. It makes a significant contribution to existing examinations of North American cities and Canadian social history through the use of categories which are rarely employed and questions that are seldom posed in investigations of working-class history during the period of industrialization. A holistic treatment of Marxist philosophy provides the theoretical underpinnings for a sensitive engagement with daily street life in an urban milieu. As a site of intense sociability, Notre-Dame Street, the main street of the industrial suburb of Saint-Henri, offers a unique perspective on the intricate use of public space and its relations to social space. This thesis covers the period between the years of town incorporation in 1875 and annexation to the City of Montreal in 1905. Notre-Dame Street underwent significant transformations in this period. A main street of a small town on the outskirts of Montreal became the principal commercial street of a bustling industrial city. The 1890s was a decade of particularly marked shifts, characterized by significant population growth and dramatic changes in physical form. Class and ethnic tensions intensified as a result. A 1891 labour dispute at Merchants Manufacturing, a textile factory, took to the streets, and the local elite contested George A. Drummond's refusal to pay municipal taxes in 1897. Resistance to monopoly control of utilities was evidenced by the use of petitions and protets or notarized letters. Workers' parties, journalists, and municipal reform leagues increasingly challenged the hegemony of the local elite whose persistent practices of overspending resulted in a substantial debt and annexation. The study of a local street in an industrializing community demonstrates the prevailing social and political distribution of wealth and power. It reveals significant differences between the various class ideologies which were played out in the management of the public space of the street. An economic liberal ideology was instrumental to the development of the modern Western city through the creation of divisions between public and private spaces. Social usage, the visible presence of the working and marginal classes and women on city streets, suggests a different reality. A reconstruction of daily street life from a diversity of written and visual sources indicates that women, men, and children inhabited and frequented homes, shops, and offices, travelling to and from work, and various places of recreation. The rhythm of everyday street life was punctuated by unusual events of a celebratory, criminal, and tragic nature, which emphasize the connections between spatial structures and subjective experience. The local management of public space thus involved class antagonisms, characterized by negotiation, transgression, and resistance. This dissertation argues that the politics of this public space benefited the class interests of a grande bourgeoisie of Montreal and a local petite bourgeoisie, to the detriment of the working classes. These conflicting class interests were played out in a variety of different ways. The exclusion and appropriation of social and symbolic spaces were characterized by distinct property ownership and rental patterns. An anglophone grande bourgeoisie of Montreal owned vacant and subdivided lots. A francophone petite bourgeoisie dominated property ownership, and a majority of renters lived in flats on the main street and on adjoining streets. The shaping of the physical infrastructure was distinguished by the growth of monopolies and minimal local intervention. The civic manifestation of the ordered and ritualistic celebration of the parade emphasized a Catholic identity. Attempts to impose an appropriate and genteel code of behaviour on city streets led to the moral regulation and social control of criminal behaviour.
Keywords: Academic Dissertation; Academic theses; Thèses et écrits académiques